HUMANIZATION: TEACHING STRATEGIES AND PERCEPTION OF NURSING STUDENTS - Oliveira Reis, Carla; Bernardes, Viviana; Ferreira, Luisa; Franco, Filipe (Health and Society, 2023)
Context: The teaching of Humanization in the context of Nursing education is fundamental to value the human, individual and ethical dimension of Nursing Care. Objective: To identify strategies in the teaching of Humanization of Nursing Care. Methodology: Scoping Review performed on the EBSCO Host), B-On, EBSCO Discovery Science and WEB OF SCIENCE databases. The descriptors used were: “Humanization Care”; Caring; Teaching; Nurs*. Papers available in full text, peer-reviewed published in the last 5 years were included. Results: Of the 19 selected articles, the importance of active methodologies and simulation using Debriefing is highlighted. Conclusion: Strategies that allow the development of reflection, communication and relationship and group dynamics, as well as the strengthening of the teacher/student relationship seem to have some evidence of effectiveness in the teaching of Humanization, however, future research is needed with research designs with more evidence.